2019
DOI: 10.1038/s41419-019-1404-9
|View full text |Cite
|
Sign up to set email alerts
|

Microglia as modulators of exosomal alpha-synuclein transmission

Abstract: Recent researches regarding to exosomal involvement in alpha-synuclein (α-syn) transmission relating to the pathological process of Parkinson’s disease (PD) have attracted considerable attention. It is highly desirable to make clear the diffusion process and cellular uptake of α-syn-associated exosomes and the underlying mechanism of exosomes-involved communication in the synucleinopathy pathogenesis. To determine the contribution of α-syn-associated exosomes to the initiation and progression of PD, plasma exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
142
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 70 publications
7
142
0
1
Order By: Relevance
“…***p < 0.001. secreted vesicle-associated α-syn appears to be internalized by primary neurons. This is in agreement with data of Xia et al, who also observed that exogenous exosomes are taken up by neuronal and microglia cells, both in vitro and in vivo (Xia et al, 2019). Moreover, human α-syn has been shown to accumulate in neuronal cells following hippocampal injection of exosomes derived from patients with dementia with LBs (DLB) (Ngolab et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…***p < 0.001. secreted vesicle-associated α-syn appears to be internalized by primary neurons. This is in agreement with data of Xia et al, who also observed that exogenous exosomes are taken up by neuronal and microglia cells, both in vitro and in vivo (Xia et al, 2019). Moreover, human α-syn has been shown to accumulate in neuronal cells following hippocampal injection of exosomes derived from patients with dementia with LBs (DLB) (Ngolab et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Together, our results, using exosomes as carrier vesicles of pathological α-syn, indicate that exosomes alone are insufficient to induce robust LB-like pathology in wt mouse brains. We should note here that irrespective of the pathogenic potential of their α-syn cargo, we and others have noticed that exosomes are taken up less efficiently from neurons than other cell types, like microglia (Xia et al, 2019). This limited access might also affect their potential to recruit the endogenous neuronal α-syn and transmit pathology in vivo.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Exosomes are produced and released by virtually all cell types, including different brain cells, such as neurons, astrocytes, microglia, and oligodendrocytes (Potolicchio et al, 2005;Fauré et al, 2006;Krämer-Albers et al, 2007;Bianco et al, 2009;Dutta et al, 2018;Goetzl et al, 2018;Xia et al, 2019). The nomenclature used in the field is somewhat problematic.…”
Section: Introductionmentioning
confidence: 99%